Computational methods in molecular biology - Salzberg, Steven L., 1960-; Searls, David B.; Kasif, Simon (Elsevier, 1998)
Computational biology is a rapidly expanding field, and the number and variety of computational methods used for DNA and protein sequence analysis is growing every day. These algorithms are extremely valuable to biotechnology companies and to researchers.
Keywords: Molecular biology -- Mathematics.; elektronické knihy; electronic books